Potential application of bitter gourd (Momordica Charantia) peel as an adsorbent for the removal of total hardness In Kangkar Senangar’s groundwater - Muhamad, Mimi Suliza; Saari, Syahira Azlin; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ali, Roslinda (Penerbit UTHM, 2020)
Lately many countries in the world are suffering with the shortage of fresh and clean drinking water as it is a source of life and energy. Rapid pace of industrialization, population expansion, and unplanned urbanization have largely contributed to the severe water pollution and surrounding soils [1]. The main sources of water pollution can be attributed by discharge of untreated sanitary and toxic industrial wastes, dumping of industrial effluent and runoff from agricultural fields. It is well known that 70–80% of all diseases in developing countries are related to water contamination, particularly that susceptible to women and children [2]. This is because water sources now become limited as drinking water quality has been reduced by pollution. Hardness is one of the problem related to unpalatable drinking water that need to be control at acceptable level.